2018
DOI: 10.1038/s41598-018-24552-3
|View full text |Cite
|
Sign up to set email alerts
|

East Asian Winter Monsoon Impacts the ENSO-related Teleconnections and North American Seasonal Air Temperature Prediction

Abstract: El Niño-Southern Oscillation (ENSO) is a key feature for seasonal weather and climate prediction in the extra-tropics since related sea surface temperature anomalies induce precipitation anomalies that generate poleward propagating Rossby waves and teleconnections. The East Asian winter monsoon (EAWM) is driven by processes originating over the Asian continent and, to a lesser degree, by ENSO-related tropical convection. EAWM also strongly affects convection and precipitation patterns over the western tropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…In this study, we focused on the EP ENSO's influence on the EAT, one member of the EAWM system, and explored the potential factors modulating the relationship between EP ENSO and the EAT. On another aspect, some other studies showed that there is a large variability of EAWM which is independent with ENSO (Ma et al, 2018;Yu and Sun, 2018). Ma et al (2018) further suggested that the EAWM variability independent of ENSO could modulate ENSO's impact on the Pacific-North American teleconnection pattern and North American winter climate.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this study, we focused on the EP ENSO's influence on the EAT, one member of the EAWM system, and explored the potential factors modulating the relationship between EP ENSO and the EAT. On another aspect, some other studies showed that there is a large variability of EAWM which is independent with ENSO (Ma et al, 2018;Yu and Sun, 2018). Ma et al (2018) further suggested that the EAWM variability independent of ENSO could modulate ENSO's impact on the Pacific-North American teleconnection pattern and North American winter climate.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…The result shows that the correlation between the two is 0.32, significant at the 99% confidence level, implying that the variabilities of ENSO and the NPO are related. To explore the solo impact of the NPO (which is independent of ENSO) on the EAT, based on previous studies (Chen et al, 2013a;Ma et al, 2018), the linear regression method is employed to remove the Niño3-related part from the NPO index, and the remainder (the NPO_res index) is used for analysis (Figure 4). Different phase combinations of the NPO_res and La Niña are shown in Table 3.…”
Section: Connection Between La Niña and The Eatmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that the ENSO is one of the strongest signals yet observed for the air-sea interaction on an interannual timescale, its occurrence results in large-scale atmospheric circulation anomalies and leads to a significant impact on the climate of many places around the world (Dai and Wigley 2000, Larkin 2005, Jia and Ge 2017, Agilan and Umamahesh 2018. Especially in China, many studies have pointed out that extreme precipitation events in most areas of China are significantly affected by ENSO (Gao et al 2006, Wang et al 2008b, Ma et al 2018a. In the warm phase years (El Niño years), there was less precipitation in southeast China, while the opposite occurred during the cold phase years (La Niña) (Jin et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As a major monsoon system, the East Asian monsoon is an important modulator of the East Asian climate, which shapes the seasonal march of major rain belts and the Meiyu-Baiu rains with its significant variability from intraseasonal to interdecadal scales [26]. It also affects the ENSO-related teleconnections that extend the influence to the global scale [39]. As PE is the reciprocal of atmospheric water residence time, its variability is closely associated with the activity of the East Asia summer monsoon (EASM) [19,21].…”
Section: Introductionmentioning
confidence: 99%